Biodegradation of low-density polyethylene film by two bacteria isolated from plastic debris in coastal beach - Rong, Zhen; Xu, Xue-Wei; Wu, Yue-Hong (Ecotoxicology and environmental safety, 2024)
Low-density polyethylene (LDPE) conduces massive environmental accumulation due to its high production and recalcitrance to environment. In this study, We successfully enriched and isolated two strains, Nitratireductor sp. Z-1 and Gordonia sp. Z-2, from coastal plastic debris capable of degrading LDPE film. After a 30-day incubation at 30 ℃, strains Z-1 and Z-2 decreased the weight of branched-LDPE (BLDPE) film by 2.59 % and 10.27 % respectively. Furthermore, high temperature gel permeation chromatography (HT-GPC) analysis revealed molecular weight reductions of 7.69 % (Z-1) and 23.22 % (Z-2) in the BLDPE film. Scanning electron microscope (SEM) image showed the presence of microbial colonization and perforations on the film's surface. Fourier transform infrared spectroscopy (FTIR) analysis indicated novel functional groups, such as carbonyl and carbon-carbon double bonds in LDPE films. During LDPE degradation, both strains produced extracellular reactive oxygen species (ROS). GC-MS analysis revealed the degradation products included short-chain alkanes, alkanols, fatty acids, and esters. Genomic analysis identified numerous extracellular enzymes potentially involved in LDPE chain scission. A model was proposed suggesting a coordinated role between ROS and extracellular enzymes in the biodegradation of LDPE. This indicates strains Z-1 and Z-2 can degrade LDPE, providing a basis for deeper exploration of biodegradation mechanisms. •Nitratireductor sp. Z-1 and Gordonia sp. Z-2 were verified to degrade LDPE.•Both strains produced ROS and released short-chain byproducts from LDPE.•Strain Z-2 achieved a significant weight loss (10.27 %) of branched-LDPE over 30 d.•The LDPE degradation model of strains Z-1 and Z-2 has been proposed.